An Analysis of Code-Switching in “Ali & Ratu Ratu Queens” Movie - Putu Rosa Natalia (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Code-switching becomes one of the phenomena that happens in society, especially for bilingualism and multilingualism. The ability to master more than one language makes a person sometimes switch from one language to another when speaking or better known as code-switching. Code-switching not only happens in real-life contexts but also happens in novels, talk shows, songs, movies, and other works. This research aimed to find out and analyze code-switching that appeared in Ali & Ratu Ratu Queens movie. In gaining the data, this study will use the qualitative descriptive method. The findings show inter-sentential code-switching is mostly used in this movie. Further, background and setting also take an important role for each of the code-switching that happens in this movie.